Patchy Bubble‐Propelled Colloids at Interfaces - David P. Rivas; Max Sokolich; Harrison Muller; Sambeeta Das (Advanced Materials Interfaces, 2023)
Abstract Liquid–liquid or liquid–air interfaces provide interesting environments to study colloids and are ubiquitous in nature and industry, as well as relevant in applications involving emulsions and foams. They present a particularly intriguing environment for studying active particles which exhibit a host of phenomena not seen in passive systems. Active particles can also provide on‐demand controllability that greatly expands their use in future applications. However, research on active particles at interfaces is relatively rare compared to those at solid surfaces or in the bulk. Here, magnetically steerable active colloids at liquid–air interfaces that self‐propel by bubble production via the catalytic decomposition of chemical fuel in the liquid medium is presented. The bubble formation and dynamics of “patchy” colloids with a patch of catalytic coating on their surface is investigated and compared to more traditional Janus colloids with a hemispherical coating. The patchy colloids tend to produce smaller bubbles and undergo smoother motion which makes them beneficial for applications such as precise micro‐manipulation. This is demonstrated by manipulating and assembling patterns of passive spheres on a substrate as well as at an air–liquid interface. The propulsion and bubble formation of both the Janus and patchy colloids is characterized and it is found that previously proposed theories are insufficient to fully describe their motion and bubble bursting mechanism. Additionally, the colloids, which reside at the air–liquid interface, demonstrate novel interfacial positive gravitaxis towards the droplet edges which is attributed to a torque resulting from opposing downward and buoyant forces on the colloids.